Finite mathematics for the managerial, life, and social sciences - Tan, S. T. (Cengage Learning, 2018)
Full of relevant, diverse, and current real-world applications that students can relate. Praised by users for its clarity, easy-to-follow writing style, and excellent applications, the texts' pedagogical features and exciting array of supplements equip students with the tools they need to make the most of their study time and succeed in the course.